Agrobacterium-Mediated Transformation Of Dendrobium Sonia-28 - Julkifle, Advina Lizah (2012)
Effective propagation of protocorm-like bodies (PLBs) of Dendrobium sonia-28 was achieved by using micropropagation technique. The highest PLBs proliferation within 21 days was observed in semi-solid media over liquid culture. Half strength of Murashige and Skoog (MS) media produced the highest PLBs growth rate percentage compared to full and double strength MS media in semi-solid and liquid cultures. In sucrose treatment, the highest PLBs growth rate percentage was in 10 g.L-1 sucrose. In the conditions of absence of sucrose (0 g.L-1) or excessive of sucrose (30 g.L-1) had proven detrimental for the PLBs growth and development.